Microhaplotypes for ancestry prediction. (December 2017) - Oldoni, Fabio; Hart, Rebecca; Long, Kelly; Maddela, Kathrina; Cisana, Selena; Schanfield, Moses; Wootton, Sharon; Chang, Joseph; Lagace, Robert; Hasegawa, Ryo; Kidd, Kenneth; Podini, Daniele
Abstract: Microhaplotypes (MHs) are loci of two or more SNPs within a short distance from each other (<300 nucleotides) with three or more allelic combinations. Massively parallel sequencing (MPS) is clonal sequencing of individual strands, thus it can distinguish the parental haplotypes at a locus. MH alleles within a locus all have the same size, do not generate stutter fragments, and have lower mutation rates than STRs. The goal of this project was to determine whether MHs could provide biogeographic ancestry prediction. A total of 278 samples including 76 African-Americans (AAs), 110 European-Americans (EAs) and 92 South West Hispanics (SWHISPs) were selected and genotyped using a 74-plex assay on the Ion Chef™ and Ion S5™ MPS platform. Results were used to generate allele frequencies for the three populations. A set of test samples (28) was genotyped and used to calculate the random match probability (RMP) in the three populations. Additionally, PHASE inferred allele frequencies from 24 populations obtained from ALFRED were used to calculate the RMP of the test samples in each population. A mixture study was also performed to evaluate the detection limit for the minor contributor of the MH 74-plex. Among the populations studied, the RMP averaged remarkably higher in each individual's self-identified population of "origin". For example, AAs had the highest RMP in African and African-American populations. In the mixture study results showed that alleles from the minor contributor were detectable at an 80:1 major/minor ratio when the input DNA was 10 ng and 40:1 when the input amount was 1 ng with a RMP equal to or greater than a typical 15 loci STR profile demonstrating that MHs can be an effective tool for ancestry prediction and mixture analysis.